(3GdeMGSHI GdeGdjI GdeJbOeI (B/s - (3GdbGVj, MSjfs; (3MeGOI, QTG s; (3OMOhM, MSjf s ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2007)
(3GdeMGSHIYf JhMjO GdGYeGd h EYOGO GdbhGFe GdeGdjI GdehMOI HJGQjN GdJhMjO aj Xd WQb GdeMGSHI Yf GdJhMjO h EYOGO GdbhGFe GdeGdjI HYO JGQjN JhMjO GdGYeGd , GdYedjGJ GdeJHGOdI GdeJYdbI HGdeNRhf , HGdGUhd GdKGHJI h GdeJYdbI HGdSfOGJ , GdJhMjO ZjQ GdeHGTQ eY eTcdGJ NGUI aj JhMjO GdGYeGd h CNjQG VQjHI GdONd aj JhMjO GdGYeGd (B.s
Keywords: (3GdeMGSHIs; (3GdeMGSHI(B- (3GdeGdjIs